2022
DOI: 10.34172/mejdd.2022.293
|View full text |Cite
|
Sign up to set email alerts
|

Esophagitis Dissecans Superficialis after COVID-19; A Case Report

Abstract: Esophagitis dissecans superficialis (EDS) is an uncommon disease characterized by esophageal mucosal sloughing. EDS is a benign condition that usually resolves without residual pathology. Medication, chemical irritants, hot drinks, and autoimmune diseases have all been associated with EDS. Here a 60-year-old lady with post-COVID-19 EDS is presented. Her chief complaint was dysphagia and odynophagia for 2 weeks duration. EDS diagnosis was based on endoscopic findings and biopsy. Her problem was improved by a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…EDS, also known as sloughing esophagitis, is a benign yet rare pathological finding with less than 100 cases described in the literature. It distinctly appears as columns of peeling mucosa with normal underlying esophageal tissue on upper endoscopy [ 1 ]. Histopathology further reveals parakeratosis and intraepithelial splitting, although it is nonspecific and can be misinterpreted as Candida esophagitis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDS, also known as sloughing esophagitis, is a benign yet rare pathological finding with less than 100 cases described in the literature. It distinctly appears as columns of peeling mucosa with normal underlying esophageal tissue on upper endoscopy [ 1 ]. Histopathology further reveals parakeratosis and intraepithelial splitting, although it is nonspecific and can be misinterpreted as Candida esophagitis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its seemingly striking appearance, complete healing without complications is frequently achieved following the withdrawal of offending agents. It mostly affects those of older age on multiple medications, although the mechanism remains unclear [ 1 , 2 ]. We present a case of an 81-year-old female diagnosed with EDS following an acute 8-pound weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the receptors of the angiotensin 2-converting enzyme are expressed in the gastric cells. Therefore, it is possible that SARS-CoV-2 can cause gastritis, PUD, GIB and in rare cases esophagitis dissecans superficialis [ 18 , 19 ]. However, the underlying mechanisms of vaccine-induced PUD are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, the oral‐coronavirus connection is unique due to the increased mortality risk and extended multiple tissue morbidity through PASC. Multiple studies have reported increased risk for respiratory, oesophageal‐intestinal, cardiovascular, renal, and neurologic‐brain disorders in COVID‐19 patients 25–30 . We propose that periopathogen‐derived metabolites and enzymes depress the host oral mucosal resistance and extend the initial oral infection systemically.…”
Section: Introductionmentioning
confidence: 88%
“…Multiple studies have reported increased risk for respiratory, oesophageal-intestinal, cardiovascular, renal, and neurologic-brain disorders in COVID-19 patients. [25][26][27][28][29][30] We propose that periopathogen-derived metabolites and enzymes depress the host oral mucosal resistance and extend the initial oral infection systemically. Further, PD pathogen-driven attenuation of host oral mucosal immunity targets the microbiome organization and perpetuates the survival of selective pathogens.…”
Section: Introductionmentioning
confidence: 99%